PLATFORM DIGITAL DAN PARTISIPASI MUZAKKI GENERASI Z: TINJAUAN SISTEMATIS BERBASIS PRISMA - Iseu Anggraeni; Syifa Vidya Sofwan; Muhammad Iqbal (Jurnal Maneksi, 2026)
Introduction: Zakat is a strategic instrument of Islamic social finance for poverty alleviation, yet Indonesia's zakat collection remains far below its estimated potential of IDR 327.6 trillion per year. Digital platforms tailored to Generation Z are widely regarded as a key lever to close this gap, but prior studies remain fragmented across single theoretical lensesMethods: A Systematic Literature Review following the PRISMA 2020 protocol was conducted across Scopus, Web of Science, Google Scholar, and DOAJ (2019-2025). From 1,247 records identified, 38 articles met all inclusion and quality criteria, assessed using MMAT and CASP.Results: Six dominant themes emerged: technology acceptance, trust and transparency, digital zakat literacy, social influence and religious motivation, platform features and user experience, and institutional governance. The Technology Acceptance Model (TAM) was the most frequently applied theory (39.5%), followed by Trust Theory (26.3%) and Theory of Planned Behavior (18.4%).Conclusion and suggestion: Six dominant themes emerged: technology acceptance, trust and transparency, digital zakat literacy, social influence and religious motivation, platform features and user experience, and institutional governance. The Technology Acceptance Model (TAM) was the most frequently applied theory (39.5%), followed by Trust Theory (26.3%) and Theory of Planned Behavior (18.4%). The study introduces an Integrated Conceptual Framework of Generation Z Digital Zakat Participation, synthesizing TAM, TPB, Trust Theory, and Digital Zakat Literacy. Findings offer practical guidance for zakat institutions, Islamic FinTech providers, and regulators, while outlining an empirically grounded agenda for future SEM/PLS-SEM validation and cross-country comparison. Keywords: Digital zakat; Generation Z; Islamic FinTech; Muzakki participation; Systematic literature review.